The Relationship Between Reading Habits and Reading Comprehension of English Department in UNTIRTA - Tri Septiarini; Aceng Rahmat; Darmahusni - (Journal of English Language Studies, 2018)
This study aims at determining whether there is a positive relationship between reading habits and reading comprehension of English Department in UNTIRTA. The study carried out in the students of the second semester in English Department at UNTIRTA. The study subjects are 98 respondents. This study used the descriptive quantitative approach with correlation analysis. Data collecting techniques are tests, questionnaires, and documentation. Technical analysis of prerequisite test data obtained from normality test, homogeneity test, and linearity test by using SPSS 23. Hypothesis test obtained from simple correlation by using SPSS 23 with a significance level of 95% (a=0,05). The study result consists of (1) A normality test showed the value of probability = 0,573 > significance level = 0,05, H0 accepted. It means that the variables data spread normally. (2) A homogeneity test showed the value of probability test = 0,587 > significance level = 0,05, H0 accepted. It means that the variables data are homogeneous. (3) Based on linearity test result, the equation is Ŷ= 7,913 +  0,148 X. (4) Based on correlation test result, Tcount = 6,571 > Ttable= 1,66. It means that there is a positive relationship between reading habits and reading comprehension of students in English Department at Untirta.